Impact of preprocedural TIMI flow on clinical outcome in low‐risk patients with ST‐elevation myocardial infarction: Results from the ATLANTIC study. Issue 3 (8th May 2019) - Bauer, Timm; Zeymer, Uwe; Diallo, Abdourahmane; Vicaut, Eric; Bolognese, Leonardo; Cequier, Angel; Huber, Kurt; Montalescot, Gilles; Hamm, Christian W.; van't Hof, Arnoud W.; ,
Abstract: OBJECTIVES: This study sought to analyze the impact of the preprocedural thrombolysis in myocardial infarction (TIMI) flow on clinical outcome in patients with ST‐elevation myocardial infarction (STEMI). BACKGROUND: Previous studies have shown that the TIMI flow 0/1 prior to primary percutaneous coronary intervention (PCI) is associated with a poor clinical outcome. However, it is unclear whether the same is true in patients with ongoing STEMI of less than 6 hr duration, rapid reperfusion, and modern guideline‐adherent therapy. METHODS: The ATLANTIC study compared prehospital versus inhospital treatment with ticagrelor in patients with acute STEMI. For this analysis, patients were divided into three groups according to the preprocedural TIMI flow grade of the infarct vessel: TIMI 0/1, TIMI 2, and TIMI 3. RESULTS: From a total of 1, 680 patients, 1, 113 had TIMI 0/1, 279 TIMI 2, and 288 TIMI 3 flow before primary PCI. At 30 days, the composite ischemic endpoint (5.5, 2.9, and 2.1%, p  < .05) and all‐cause death (3.0, 1.4, and 2.1%, p  = .30) were highest in patients with TIMI flow 0/1. After adjustment, preprocedural TIMI flow <3 (versus 3) was not an independent predictor of major adverse ischemic events within 30 days (odds ratio 1.89, 95% confidence interval 0.74–4.85). However, definite stent thrombosis occurred only in patients with initial TIMI flow 0/1 (1.0%). Among these patients, those with prehospital administration of ticagrelor were less often affected (0.3% vs. 1.3%, p  < .05). CONCLUSION: In this post‐hoc analysis, preprocedural TIMI flow was not independently associated with a higher rate of adverse ischemic events.